2018
DOI: 10.1021/jacs.7b11926
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Photolyase’s DNA Repair Mechanism in Mesophiles and Extremophiles

Abstract: Light-driven DNA repair by extremophilic photolyases is of tremendous importance for understanding the early development of life on Earth. The mechanism for flavin adenine dinucleotide repair of DNA lesions is the subject of debate and has been studied mainly in mesophilic species. In particular, the role of adenine in the repair process is poorly understood. Using molecular docking, molecular dynamics simulations, electronic structure calculations, and electron tunneling pathways analysis, we examined adenine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(60 citation statements)
references
References 79 publications
(154 reference statements)
3
55
2
Order By: Relevance
“…Considerable protein motions that reorganize redox active amino acids or cofactors are known to affect electron-transfer rates in flavoprotein BLUF domains 38 and may also be in play in FAD-dependent DNA photolyase. 39,40 Molecular dynamics simulations predict similar motion in Arabidopsis cryptochrome and photolyase. 39,41 With redox center dimensions of 8 and 5 Å for the riboflavin and tryptophan respectively, rotations about the beta carbons could in principle sample donor-acceptor edge-to-edge distances from van der Waals contact to ~17 Å (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Considerable protein motions that reorganize redox active amino acids or cofactors are known to affect electron-transfer rates in flavoprotein BLUF domains 38 and may also be in play in FAD-dependent DNA photolyase. 39,40 Molecular dynamics simulations predict similar motion in Arabidopsis cryptochrome and photolyase. 39,41 With redox center dimensions of 8 and 5 Å for the riboflavin and tryptophan respectively, rotations about the beta carbons could in principle sample donor-acceptor edge-to-edge distances from van der Waals contact to ~17 Å (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…39,40 Molecular dynamics simulations predict similar motion in Arabidopsis cryptochrome and photolyase. 39,41 With redox center dimensions of 8 and 5 Å for the riboflavin and tryptophan respectively, rotations about the beta carbons could in principle sample donor-acceptor edge-to-edge distances from van der Waals contact to ~17 Å (Fig. 7).…”
Section: Discussionmentioning
confidence: 98%
“…This result indicates that the T DA value might decrease when the adenine moiety is located away from CPD. Rousseau et al also reported that the contribution of the superexchange mechanism decreased when the adenine moiety was separated from CPD [39]. Therefore, the adenine moiety is very important for the ET reaction.…”
Section: Electron Transfer Reactivity For Cryptochrome-dashmentioning
confidence: 96%
“…Although the outline of the DNA repair mechanism for CPD-PLs has been revealed during the last two decades by theoretical [29][30][31][32][33][34][35][36][37][38][39] and experimental studies [23][24][25][26][40][41][42][43][44][45], there is room for further research on the DNA repair mechanism because the primary process in the DNA repair reaction, i.e., the recognition of UV-induced DNA lesions by PLs, is not clearly…”
Section: Introductionmentioning
confidence: 99%
“…The authors conclude to the coexistence of the two mechanisms, in agreement with experiments. The comparison of a set of four CPD photolyases from mesophiles and (hyper)-thermophiles species, based on classical MDs and electron tunneling analysis, shows that the adenine significantly contributes to the electronic coupling of the electron transfer to the damage in the most rigid proteins [127]. At higher temperature, water molecules can compete with adenine to form the best tunneling pathway.…”
Section: Dna Photolesions Repairmentioning
confidence: 99%